2014
DOI: 10.1103/physrevb.90.125447
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule magnetMn12on graphene

Abstract: We study energetics, electronic and magnetic structures, and magnetic anisotropy barriers of a monolayer of single-molecule magnets (SMM), [Mn 12 O 12 (COOR) 16 ](H 2 O) 4 (abbreviated as Mn 12 , with R=H, CH 3 , C 6 H 5 and CHCl 2 ), on a graphene surface using spin-polarized density-functional theory with generalized gradient corrections and the inclusion of van der Waals interactions. We find that Mn 12 molecules with ligands -H, -CH 3 , and -C 6 H 5 are physically adsorbed on graphene through weak van … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…There should not be much difficulty in realizing strain in a graphene system. In addition, there are theoretical works which deal with effects of magnetic impurities on electronic transport in graphene, see refs 26,32,33,45,46 . In ref.…”
Section: Experimental Realizationmentioning
confidence: 99%
“…There should not be much difficulty in realizing strain in a graphene system. In addition, there are theoretical works which deal with effects of magnetic impurities on electronic transport in graphene, see refs 26,32,33,45,46 . In ref.…”
Section: Experimental Realizationmentioning
confidence: 99%
“…To characterize the origin of the AF ground state of Ce 3 Mn 8 , the magnetic properties of Ce 3 Mn 8 were calculated within the framework of Kohn–Sham density functional theory (DFT), using atomic coordinates for the molecule taken from the crystal structure. DFT based methods have been widely used for studying molecular magnets with Mn centers 26 – 31 . First-principles calculations were performed for eight different spin configurations of Ce 3 Mn 8 molecules, corresponding to FM, A-AF, C-AF, and G-AF spin alignments ( Supplementary Methods ), with all three orientations of the ferromagnetic planes (A-AF) or axes (C-AF) considered and neglecting any noncolinearity (the easy axis is assumed to be along the global z axis).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that charging is an effective way to tune the magnetic anisotropy of a magnetic molecule; 107 and we have previously simulated the electron transfer between graphene and Mn 12 molecules without a gate field. 108 Following this thread, we started investigations to address how charge doping affects the magnetic anisotropy of single-molecule magnets such as Mn 12 . A glance in the field of first-principles transport studies, there is very little theoretical work 109,110 addressing the role of spin-orbit coupling of molecules or 2D junction under finite gate or bias voltages.…”
Section: Conclusion Discussion and Outlookmentioning
confidence: 99%